Exploring Technology Readiness and Acceptance of Small-scale Farmers in Sabah towards the Adoption of Internet of Things Technology - Mohd Yaakub, Nurul Alam; Sumin, Viduriati; Ung, Ling Ling (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to explore and propose a conceptual framework to study the determinants of Internet of Things (IoT) adoption intention of small-scale farmers in Sabah for their farming practices. Report from Twelfth Malaysia Plan presented a tremendous decrease of workforce in agriculture sector over the years. In addition, in this contemporary era marked by technological advancements, all industry players in the agriculture sector are compelled to integrate new technologies relevant to agrobusiness. Hence, there is an urgent need of intervention to solve this issue as it will affect food production in Malaysia in the near future. The objective of this study is to formulate a conceptual framework based on semi-structured literature reviews on agricultural technology, incorporating theoretical frameworks from case studies, government reports and statistics. The paper discusses on which framework and its mode of integration that could be adopted in order to study the intention of IoT adoption among small scale farmers in Sabah. This initial conceptual framework provides insights into the needs and concerns of small-scale farmers regarding IoT adoption, serving as a guide for IoT service providers and policymakers in shaping initiatives for agricultural transformation in Sabah.